Ampera dan Perubahan Orientasi Ruang Perdagangan Kota Palembang 1920an-1970an - Melisa Melisa (Lembaran Sejarah, 2012)
This research examines the imaginary role of the Ampera Bridge in the city of Palembang in the changes of space orientation in trades. The unifcation of the upstream and the downstream areas of Musi River, followed by some improvements of the transportation infrastructure resulted in the modernization of the city of Palembang. The erection of the Ampera Bridge, a hub connecting the upstream and the downstream areas, created new orientation of space in the minds of traders. Trading activities, which had mainly followed the water way, underwent a transformation where both water and land ways served as effective paths.